The role of proteinuria on a simple urinalysis in neonatal hypoxic–ischemic encephalopathy: association with clinical and neurodevelopmental outcomes - Ya-Chun Hu; Ya-Chun Hu; Ya-Chun Hu; Ji-Nan Sheu; Ji-Nan Sheu; Ji-Nan Sheu; Inn-Chi Lee; Inn-Chi Lee; Inn-Chi Lee (Frontiers in Neurology)
BackgroundEarly diagnosis and initiation of hypothermia therapy for neonatal hypoxic–ischemic encephalopathy (HIE) are critical within the first 6 h after birth. Collecting urine, especially from neonates with HIE, can be challenging and time-consuming post-birth due to the likelihood of renal injury.PurposeWe assessed whether urine protein levels, measured via a simple urinalysis on the first day, could correlate with the outcomes of neonatal HIE.MethodsWe conducted urine analyses of patients with neonatal HIE on the first day to establish a correlation between the severity of HIE and neurodevelopmental outcomes at ≥1 year of age. Eighty-three patients were enrolled, encompassing cases of mild (n = 37), moderate (n = 30), and severe (n = 16) HIE. Three cases were excluded due to mortality caused by severe HIE with associated auria. Based on urine protein levels, patients were grouped as 0 to 30 mg/dL (group 1), 30 to 100 mg/dL (group 2), 100 to 300 mg/dL (group 3), and ≥ 300 mg (group 4).ResultsUrine protein levels were correlated with serum lactic acid levels [p = 0.006; r (81) = 0.304; n = 83], clinical staging [p = 0.001; r (81) = 0.36], and neurodevelopmental outcomes at ≥1 year of age [X2 (3, n = 83) = 11.35; p = 0.009]. The odds ratio for moderate-to-severe HIE in group 4 patients was 7.66 [p = 0.010; 95% confidence interval (CI), 1.61–36.33] compared with those in groups 1–3. Those in group 4 had a high positive predictive value (87.50%) and high specificity (94.59%).ConclusionElevated urine protein levels observed in the first urinalysis conducted on the day after birth were found to be associated with serum lactic acid levels, clinical staging, and neurodevelopmental outcomes at ≥1 year of age.